2008
DOI: 10.3390/md6020103
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intracellular and Extracellular Saxitoxin Levels in Both Field and Cultured Alexandrium spp. Samples from Sequim Bay, Washington

Abstract: Traditionally, harmful algal bloom studies have primarily focused on quantifying toxin levels contained within the phytoplankton cells of interest. In the case of paralytic shellfish poisoning toxins (PSTs), intracellular toxin levels and the effects of dietary consumption of toxic cells by planktivores have been well documented. However, little information is available regarding the levels of extracellular PSTs that may leak or be released into seawater from toxic cells during blooms. In order to fully evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For example, in Sequim Bay, Washington, the gonyautoxins GTX1, 4, GTX2, 3, and neosaxitoxin were more prevalent in Alexandrium spp. isolates compared to saxitoxin itself (Lefebvre et al 2008). Further, detection of algal toxins in the scats remains an underestimate of the full amount of toxins the sea lions were exposed to because it only reflects the toxin that was passed through digestion and does not account for the amount initially ingested.…”
Section: Study Limitationsmentioning
confidence: 99%
“…For example, in Sequim Bay, Washington, the gonyautoxins GTX1, 4, GTX2, 3, and neosaxitoxin were more prevalent in Alexandrium spp. isolates compared to saxitoxin itself (Lefebvre et al 2008). Further, detection of algal toxins in the scats remains an underestimate of the full amount of toxins the sea lions were exposed to because it only reflects the toxin that was passed through digestion and does not account for the amount initially ingested.…”
Section: Study Limitationsmentioning
confidence: 99%
“…in shellfish but is also extracted in surrounding water [23]. The isolation of STX could be made from any matrixes but the concentration of toxin and their stability is much lower in water samples than in algal or cyanobacteria samples.…”
Section: Stx Occurs In Algal and Cyanobacterial Cells And Is Accumulatedmentioning
confidence: 99%
“…In a few studies with bivalves, a column with activated charcoal was used to adsorb dissolved PSTs for sub sequent elution and analysis (Sekiguchi et al 2001, Suzuki et al 2003, Asakawa et al 2006. A recent study by Lefebvre et al (2008) using a receptor-binding assay (RBA) and an enzyme-linked immunosorbent assay (ELISA) found extracellular PSTs in both field samples and laboratory cultures. Activated charcoal is used to re move saxitoxin in freshwater treatments (Falconer et al 1989, Orr et al 2004, but this treatment is not 100% effective (Newcombe & Nicholson 2002, 2004, Orr et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to use activated charcoal columns to collect the toxins, as has been done in some studies with bivalves (Sekiguchi et al 2001, Suzuki et al 2003, Asakawa et al 2006. Lefebvre et al (2008) measured the extracellular toxin levels in both field samples and laboratory cultures by receptor binding assay (RBA) and enzyme-linked immunosorbent assay (ELISA). This study showed that extracellular PSTs were present during blooms of Alexandrium spp., and in culture media.…”
Section: Introductionmentioning
confidence: 99%